Post-secularity in Emile Habiby’s The Secret Life of Saeed, the Ill-Fated Pessoptimist - Yu Kao, Peter Chien (Advances in Humanities and Contemporary Studies, 2023)
Post-secularity helps elaborate one’s individual self-identity in twentieth century. With the wave of "re-enchantment," one’s individual self-identity is much complicated by religion, nationalism, and racial and ethnic backgrounds and all are characteristic entanglements of the 1848 and 1967 Israel-Palestine Wars. What this paper will explore is war-time survivors’ individual self-identity in the historical context of the 1948 and 1967 Israel-Palestine Wars in Emile Habiby’s The Secret Life of Saeed, the Ill-Fated Pessoptimist. The dual/ oppositional forces during the period of Israel-Palestine 1948 & 1976 Wars through Emile Habiby’s The Secret Life of Saeed, the Ill-Fated Pessoptimist (1974) will be examined. Despite the fact that the previous studies tend to direct to the causes of Wars to be "state penetration," "the settlement project," and "military occupation," it is still unclear about how Israeli and Palestinian civilians’ individual self-identity is shaped by the Wars. Therefore, the author intends to infuse this paper with a certain analysis of post-secular theories so as to complement what is deemed incomplete when Israeli-Palestinian Wars are criticized for its discussion in war studies and the realm of international relations and politics. Fictional narrative and oral testimonies are provided to represent the war-time reality in the novel. It is argued that Saeed’s (protagonist’s) individual Palestinian self-identity is constructed not only by religion and territory, but also by history and Saeed’s self-perception and self-recognition towards multiple self-identity. Habiby’s writing technique, the adoption of satire, also helps shape Saeed’s self-identity through his name in a paradoxical way: Saeed as Pessoptimist, a mix of pessimism and optimism. Secularization theories based on modernity project helps contextualize the relationship between religion and Israel as nation state. Postsecular theories seek to provide alternative interpretive way to elaborate Saeed as Israeli and simultaneously Palestinian and his self-identity through the narratives and testimonies.